2020
DOI: 10.3390/jcm9020577
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Sparing Robot-Assisted Radical Cystectomy with Intracorporeal Padua Ileal Neobladder in Female: Surgical Technique, Perioperative, Oncologic and Functional Outcomes

Abstract: Our aim was to illustrate our technique of sex-sparing (SS)-robot-assisted radical cystectomy (RARC) in female patients receiving an intracorporeal neobladder (iN). From January 2013 to June 2018, 11 female patients underwent SS-RARC-iN at a single tertiary referral center. Inclusion criteria were a cT ≤ 2 N0 M0 bladder tumor at baseline imaging (CT or MRI) and an absence of tumors in the bladder neck, trigone and urethra at TURB. Baseline, perioperative, and outcomes at one year were reported. The median oper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 26 publications
(34 reference statements)
0
38
0
Order By: Relevance
“…All these findings together bolster the assertion that meticulous ureteral handling, along with fine suturing technique of Wallace uretero-ileal anastomosis and shorter intestinal chimney, are essential to minimize the risk of postoperative strictures, urinary leakage and VUR. However, studies presenting different techniques of uretero-ileal anastomosis and orthotopic reservoir construction, showed comparable results in regard to early and late postoperative complications rate (18,19).…”
Section: Discussionmentioning
confidence: 98%
“…All these findings together bolster the assertion that meticulous ureteral handling, along with fine suturing technique of Wallace uretero-ileal anastomosis and shorter intestinal chimney, are essential to minimize the risk of postoperative strictures, urinary leakage and VUR. However, studies presenting different techniques of uretero-ileal anastomosis and orthotopic reservoir construction, showed comparable results in regard to early and late postoperative complications rate (18,19).…”
Section: Discussionmentioning
confidence: 98%
“…At 12 months, day and night-time continence rates were 91% and 86%, respectively; however, the exact definition of continence was not specified. 22 In contrast, in a study of 13 female patients with Padua neobladder by Simone et al reported day and night-time continence at 46% and 39%, respectively (utilizing zero pads/day). 23 As part of assessing UF, some studies evaluated the need for ISC after RARC.…”
Section: Urinary Functionmentioning
confidence: 91%
“…In one study, ISC was required in three out of 11 women who underwent RARC and neobladder. 22 It is still unknown if there are any patient or disease-related factors associated with the need for ISC. Studies examining urodynamics after RARC are scarce.…”
Section: Urinary Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, functional outcomes after radical cystectomy need to be further reported and investigated to increase the quality of life of BCa patients. Tuderti et al [7] reported their experience of patients treated with sex sparing robot-assisted radical cystectomy in female patients receiving an intracorporeal neobladder reporting good oncological and functional outcomes 12 months after treatment. From the same institution, Claroni et al [8] reported on recovery outcomes from anesthesia after robotic-assisted RC.…”
mentioning
confidence: 99%